Religious Pluralism Discourse in Public Sphere of Indonesia: A Critical Application of Communicative Action Theory to Inter-religious Dialogue - Sung Min Kim; J.B. Banawiratma; Dicky Sofjan (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2020)
This paper examines religious pluralism discourse in post-Reformasi Indonesia. Though there is general consensus about the importance of maintaining inter-religious harmony, there are still various perspectives and arguments on the idealization of dealing with religious diversity in society. The differences are found not only between the advocates and opponents of religious pluralism but also among proponent groups of religious pluralism. This paper looks at how religious organizations for inter-religious harmony struggle for legitimating their religious pluralism ideals in society. In this context, this paper, by using Habermas’ theory of communicative action, focuses on the characteristics of their efforts to communicate with others in the public sphere. It examines inter-faith dialogue done by NGOs’ activities and arguments, focusing on their validity claims for justifying religious pluralism. This paper argues that some conceptions and presuppositions of this theory need to be critically assessed and modified in analyzing these NGOs’ discourse so that it can be appropriately applied to the Indonesian context in which religion has substantial power to influence people’s thoughts and behaviors. Particularly it will point out 1) the problem of universalized rationality, 2) power relation and strategic action, and 3) the role of religious reason in public discourse. [Artikel ini mengkaji diskursus pluralisme agama di era pasca-Reformasi Indonesia. Meski ada kesepakatan akan pentingnya membangun harmoni lintas agama, tapi pada tataran praktiknya masih ada pelbagai perspektif dan argumentasi dalam menyikapi keanekaragaman agama dalam masyarakat. Perbedaan ini tidak hanya ditemukan di kalangan mereka yang kontra, tapi juga di kalangan mereka yang pro pluralisme agama. Artikel ini bermaksud meneliti bagaimana organisasi agama yang memperjuangkan harmoni lintas agama berjuang memancang ide-ide ideal mereka terkait pluralisme agama di masyarakat. Dalam konteks ini, penelitian ini mengacu pada teori communicative action-nya Habermas dan fokus memantau karakteristik organisasi-organisasi tersebut dalam berinteraksi satu sama lain di ruang publik. Artikel ini bermaksud menguji sejauh mana dialog antar-agama dilakukan oleh organisasi-organisasi ini, terutama validitas klaim mereka dalam menjustifikasi pluralisme agama. Artikel ini berargumen bahwa konsepsi dan asumsi dari teori-teori tersebut perlu ditinjau ulang secara kritis untuk bisa diterapkan dalam konteks Indonesia, di mana agama masih memiliki kekuatan potensial untuk mempengaruhi pemikiran dan perilaku masyarakat. Secara khusus artikel ini akan membahas 1) problem rasionalitas universal, 2) relasi kuasa dan aksi strategis, serta 3) peran logika agama di ruang (diskursus) publik.